Force coordination in static manipulation: Discerning the contribution of muscle synergies and cutaneous afferents - de Freitas, Paulo Barbosa; Markovic, Goran; Krishnan, Vennila; Jaric, Slobodan (Neuroscience letters, 2008)
Both an elaborate coordination of the hand grip force ( G; normal component of force acting at the digits–object contact area) and load force ( L; tangential component), and the role of cutaneous afferents in G– L coordination have been well documented in a variety of manipulation tasks. However, our recent studies revealed that G– L coordination deteriorates when L consecutively changes direction (bidirectional tasks; e.g., when vigorously shaking objects or using tools). The aim of the study was to distinguish between the possible role of the synergy of hand grip and arm muscles (exerting G and L, respectively) and the role of cutaneous afferent input in the observed phenomenon. Subjects ( N = 14) exerted sinusoidal L pattern in vertical direction against an externally fixed device in trials that gradually changed from uni- to fully bidirectional. In addition, a manipulation of an external arm support decoupled L measured by the device (and, therefore, recorded by the cutaneous receptors) from the action of arm muscles exerting L. The results revealed that switching from uni- to bidirectional tasks, no matter how low and brief L exertion was in the opposite direction, was associated with an abrupt decrease in G– L coordination. This coordination remained unaffected by the manipulation of external support. The first result corroborates our previous conclusion that the force coordination in uni- and bidirectional manipulation tasks could be based on partly different neural control mechanisms. However, the second finding suggests that the studied control mechanisms could depend more on the cutaneous afferent input, rather than on the synergy of the muscles exerting G and L.